2005
DOI: 10.1172/jci23493
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of IKK2 in hepatocytes does not sensitize these cells to TNF-induced apoptosis but protects from ischemia/reperfusion injury

Abstract: The inhibitor of NF-κB (I-κB) kinase (IKK) complex consists of 3 subunits, IKK1, IKK2, and NF-κB essential modulator (NEMO), and is involved in the activation of NF-κB by various stimuli. IKK2 or NEMO constitutive knockout mice die during embryogenesis as a result of massive hepatic apoptosis. Therefore, we examined the role of IKK2 in TNF-induced apoptosis and ischemia/reperfusion (I/R) injury in the liver by using conditional knockout mice. Hepatocyte-specific ablation of IKK2 did not lead to impaired activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
111
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(115 citation statements)
references
References 50 publications
(36 reference statements)
4
111
0
Order By: Relevance
“…33 Because concanavalin-A provides a model for T cell-mediated hepatocyte death, it is possible that IKK␤-driven activation of NF-B functions as an important hepatocyte survival signal in alcoholic and viral liver disease. However, Luedde et al 34 did not observe enhanced susceptibility to concanavalin-A-induced apoptosis in their hepatocyte-targeted ikk␤ knockout mice. Two studies published very recently in Gastroenterology provide some answers to this conundrum.…”
Section: Nf-b As a Tumor Suppressor In Hepatocytesmentioning
confidence: 88%
See 1 more Smart Citation
“…33 Because concanavalin-A provides a model for T cell-mediated hepatocyte death, it is possible that IKK␤-driven activation of NF-B functions as an important hepatocyte survival signal in alcoholic and viral liver disease. However, Luedde et al 34 did not observe enhanced susceptibility to concanavalin-A-induced apoptosis in their hepatocyte-targeted ikk␤ knockout mice. Two studies published very recently in Gastroenterology provide some answers to this conundrum.…”
Section: Nf-b As a Tumor Suppressor In Hepatocytesmentioning
confidence: 88%
“…14,32 Similarly, 2 independent laboratories confirmed that mice with hepatocyte-targeted deletion of ikk␤ (ikk␤ hep ) develop with normal liver structure and function and do not display elevated susceptibility to hepatocyte apoptosis induced by soluble TNF-␣ or lipopolysaccharide. 33,34 It is concluded that the canonical IKK␤ driven NF-B pathway is not essential for hepatocyte survival in the normal liver or upon challenge from physiological doses of endotoxin or TNF-␣.…”
Section: Nf-b As a Tumor Suppressor In Hepatocytesmentioning
confidence: 99%
“…A continuous activation was detected at low levels after PH while a delayed and more pronounced activation could be seen after SH. While basal activation of NF-κB may be sufficient and important for regeneration and structural reformation after 70% resection [29] , the strong NF-κB activation in animals with 90% hepatectomy may also favor inflammatory processes in the damaged tissue, which counteract the restoration of a functional liver [21,30,31] .…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the role of proregenerative cytokines (e.g. IL-6 and TNF-a) and the role of transcription factors such as NF-κB are ambiguous [5,[20][21][22] .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, recruitment and activation of inflammatory cells (CD4 ϩ T lymphocytes), as well as Kupffer cells and platelet adhesion in the sinusoidal lining, have been involved in sinusoidal endothelial cell death and hepatic I/R injury. [1][2][3][4] Molecular events include nuclear factor kappaB (NF-B) activation, tumor necrosis factor (TNF) generation, JNK activation, mitochondrial permeability transition (MPT), and reactive oxygen species overproduction. [5][6][7][8] Sphingolipids, ceramide in particular, have emerged as signaling lipid intermediates that play a role in the stress response, and as mediators of apoptosis and autophagic cell death (type II programmed cell death).…”
mentioning
confidence: 99%